ANALISIS KESALAHAN KALIMAT BAHASA JEPANG MAHASISWA SASTRA JEPANG UNIVERSITAS BRAWIJAYA (KAJIAN MORFOLOGI DAN SINTAKSIS) - WAHYUNI, IIS (Jurnal Ilmiah Mahasiswa FIB, 2013)
When someone learn foreign language, sometimes learners do error. If its error did not corrected as soon as possible, it will repeat again continuesly. Therefore the writer interest to research language error analysis morphology and syntax in brawijaya university japanese literature students. There are six error sentence type that found in research result : omission error sentence type, addition error sentence type,  mistake formation error sentence type, confusion error sentence type, position error sentence type, the other error sentence type. Based on six error sentence type, include to morphology error are omission error sentence type, addition error sentence type,  mistake formation error sentence type, the other error sentence type. And then include to syntax error are addition error sentence type,  confusion error sentence type, position error sentence type, the other error sentence type. Keyword : language error, morphology error, syntax error, japanese language           proficiency test level 3, sentences making